Do verdadeiro e do falso: meditação quarta na teoria do conhecimento de René Descartes - Costa, Zeneide Gomes da (2011)
The aim of this research is to analyze the Theory of Knowledge presented in the book Meditations on First Philosophy written by French Philosopher Rene Descartes. The study comprehends a brief exploration of his philosophical work, followed by the analysis of the six Meditations. The Meditation IV Concerning the True and the False will be specifically explored in its epistemological and ontological aspects